Odds against tomorrow - McGivern, William P. 1922-1982; Lewis, John 1920-2001 (Metro-Goldwyn-Mayer Studios, 2016)
"Drei gestrandete Existenzen, zwei Weiße und ein Schwarzer, verbünden sich zu einem Banküberfall - ein Unternehmen, das scheitert und das zwei von ihnen auf Grund rassistischer Vorurteile mit dem Tod bezahlen. Spannender, perfekt inszenierter Thriller, der an Vorbilder aus der "Schwarzen Serie" Hollywoods anknüpft. Die Einbeziehung des Rassenproblems dient zwar vornehmlich dazu, die Uneinigkeit der Verbrecher in einer neuen Genre-Variante zu motivieren, doch die psychologischen Akzente sind durchaus geschickt gesetzt und verdichten sich zur sozialen Anklage." [filmdienst.de]
Original: USA 1959
special features: presented in both High Definition and Standard Definition ; original theatrical trailer ; "'Odds against tomorrow' post-screening Q&A with Harry Belafonte" (2009, 50 mins): an in-depth interview filmed at the Noir City: Chicago film festival ; "Adrian Wootton on 'Odds against tomorrow'" (2016, 30 mins): a newly filmed appreciation ; "The Guardian interview: Robert Wise at the National Film Theatre" (1995, 74 mins): a career-spanning onstage interview ; "The John Player lecture: Robert Ryan at the National Film Theatre" (1969, 63 mins): the actor talks at length about his craft ; illustrated booklet with new writing by Tega Okiti, and full film credits
Keywords: Film